2017
DOI: 10.1002/fut.21881
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting using alternative measures of model‐free option‐implied volatility

Abstract: This paper evaluates the performance of various measures of model‐free implied volatility in predicting returns and realized volatility. The critical role of the out‐of‐the money call options is highlighted through an investigation of the relevance of different components of the model‐free implied volatility. The Monte Carlo simulations show that: first, volatility forecasting performance of various measures can be enhanced by employing an interpolation‐extrapolation technique; second, for most measures consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Thereby, the sample comprises 168 observations. Following Andersen et al (2015) and Yao and Izzeldin (2018), we consider a replicated VIX index, RX, using the exact CBOE procedure every day. The RX provides an equivalent of the VIX using SPX option prices from the Optionmetrics data set.…”
Section: Datamentioning
confidence: 99%
“…Thereby, the sample comprises 168 observations. Following Andersen et al (2015) and Yao and Izzeldin (2018), we consider a replicated VIX index, RX, using the exact CBOE procedure every day. The RX provides an equivalent of the VIX using SPX option prices from the Optionmetrics data set.…”
Section: Datamentioning
confidence: 99%
“…Then lots of researchers use realized volatility to measure volatility. RV becomes one of the most popular proxies for volatility (see, for example, Buncic & Gisler, 2017;Luo & Qi, 2017;Shin & Zhong, 2017;Wang, Wu, & Xu, 2015;and Yao & Izzeldin, 2018). Andersen, Bollerslev, Diebold, and Labys (2003); Andersen, Bollerslev, and Meddahi (2004) strongly suggested that simple models with RV are better than popular GARCH-class models for volatility prediction.…”
Section: Introductionmentioning
confidence: 99%
“…long horizons. Yao and Izzeldin (2018) further extended the work of Zhang, Taylor, and Wang (2013) and evaluated the performance of various measures of model-free implied volatility in predicting returns and realized volatility. In this paper, we prefer the model-free integrated implied volatility, but we use a discrete form of the integral and consider the process risk-neutral.…”
mentioning
confidence: 99%